2005
DOI: 10.1186/gb-2005-6-8-r71
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of the murine hematopoietic system

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. MiRNA profiling of the murine hematopoietic system

The first report of systematic miRNA profiling in cells of the hematopoietic system suggests that, in addition to regulating commitment to particular cellular lineages, miRNAs might have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
142
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(151 citation statements)
references
References 39 publications
9
142
0
Order By: Relevance
“…It has been reported that miR-146a expression might be involved in cell fate determination in mouse lymphocytes, because its level is substantially increased in T helper 1 cells and decreased in T helper 2 cells relative to its expression in naïve T cells (14). T helper 1 differentiation and secretion of IFN␥ by this T cell subset are controlled primarily by the synergistic action of the IL-12 and IL-18 cytokines (42), thus suggesting a possible explanation for the elevated levels of miR-146a in T helper 1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that miR-146a expression might be involved in cell fate determination in mouse lymphocytes, because its level is substantially increased in T helper 1 cells and decreased in T helper 2 cells relative to its expression in naïve T cells (14). T helper 1 differentiation and secretion of IFN␥ by this T cell subset are controlled primarily by the synergistic action of the IL-12 and IL-18 cytokines (42), thus suggesting a possible explanation for the elevated levels of miR-146a in T helper 1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miR-146, like many mammalian miRNAs, may target a wide spectrum of gene targets, suggesting that it could be involved in regulation of multiple independent physiological processes. It is noteworthy that miR-146 already has been implicated in a number of cellular processes (14,40,41), and it will be important to determine whether all of them converge on TRAF6 and IRAK1 and perhaps a few other targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Northern blot analysis has the advantage of simultaneously detecting the mature miRNAs and miRNA precursors, but it is a very laborintensive approach. As a result, a number of different miRNA array platforms have been developed (Krichevsky et al 2003;Babak et al 2004;Calin et al 2004;Liu et al 2004;Nelson et al 2004;Sempere et al 2004;Sioud and Rosok 2004;Jiang et al 2005;Liang et al 2005;Lim et al 2005;Monticelli et al 2005;Shingara et al 2005;Castoldi et al 2006;Grundhoff et al 2006; Lee et al 2006;Mattie et al 2006;Tang et al 2006;Wang and Wang 2006;Zhao et al 2006;Wang et al 2007). The earliest prototype array for miRNA expression using isotope labeling was straightforward (Krichevsky et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…miR-146a induction in mouse CD4 and CD8 T cells depends on NF-B We and others have reported the expression of miR-146a in mouse peripheral CD4 + T cells, particularly in CD4 + CD25 + T reg cells (Monticelli et al, 2005;Lu et al, 2010;Boldin et al, 2011). Further analysis of other T cell compartments revealed that miR-146a is also highly expressed in mouse CD8 + T cells, as well as non-T reg CD4 + T cells (CD4 + CD25  ), albeit at a lower level in CD4 + CD25  T cells than in CD4 + CD25 + T reg cells and at a slightly lower level in CD8 + T cells than in CD4 + CD25  T cells (Fig.…”
mentioning
confidence: 99%